Tekst, povijest, identitet: književni rad Stanka Andrića - Rafolt, Leo (Array, 2003)
In this article author argues the concepts of fiction and faction, history and autobiography in literary works of Stanko Andrić. The article focuses on three major problems – text, history and identity – as key concepts of Andrić's literary production.